Pengaruh Tingkat Kecanduan Game Online Terhadap Empati Peserta Didik Sekolah Dasar - Indri Ayu Futri; Lukman Ismail; Ulfayani Hakim (Indonesian Journal Publisher, 2026)
The This research is motivated by the increasing use of online games among elementary school students which has a negative impact on children's empathy. Preliminary observations at SD Muhammadiyah Perumnas indicated that most fifth-grade students spent excessive time playing online games, thereby neglecting social interactions. This study aims to examine the effect of online game addiction level on the empathy of students at SD Muhammadiyah Perumnas. The method used was a quantitative approach with a correlational ex post facto design. The population and sample of the study consisted of 20 fifth-grade students using total sampling technique. Data collection instruments included validated online game addiction questionnaires and empathy questionnaires based on Likert scale. Data were analyzed using the Pearson Product Moment correlation technique. The results showed that the correlation coefficient (rxy) = -0.928, indicating a very strong negative relationship between online game addiction level and students' empathy. The contribution of the online game addiction variable to empathy was 86%. Based on the hypothesis test, rhitung (0.928) > rtabel (0.444) at significance level 5%, indicating a significant effect of online game addiction level on the empathy of students at SD Muhammadiyah Perumnas.